(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of carotid artery disease and its associated risk factors in patients with ischemic stroke at a tertiary care hospital. Design: Cross-sectional study Place and duration of the study: Department of Medicine, Aga Khan University Hospital, Karachi from 26-May-2023 to 25-Nov-2023. Methods: The study included 150 patients of both genders, their age varies between 18 - 90 years, admitted with confirmed ischemic stroke. Patients with hemorrhagic stroke, space-occupying lesions, brain infections, or septic emboli were excluded. Data on demographics, comorbidities, and carotid Doppler ultrasound to assess the presence and degree of carotid artery disease were collected on structured proforma. The degree of stenosis was categorized as mild (<50%), moderate (50–69%), or severe (≥70%). Statistical analysis was performed using SPSS version 24. Chi-square test used to identify risk factors. A p-value <0.05 was considered significant. Results: The mean age was 65.8 ± 13.9 years, and 64.7% were male. Hypertension 78.0%, diabetes 44.7%, and hyperlipidemia 36.7% were common comorbidities. Carotid artery disease was present in 53.3% of the participants, Carotid stenosis was present in 32% of the participants, while 10.0% had severe stenosis. In terms of ethnicity, Mohajirs were the largest group, representing 34.7% of the participants, followed by Sindhis at 23.3%, and Punjabis at 18.0%. Significant associations with carotid artery disease were observed for older age (p = 0.040), higher BMI (p = 0.005), and smoking history (p < 0.001). Conclusion: A notable proportion of ischemic stroke patients had underlying carotid artery disease, particularly those who were older, obese, or smokers. The findings of this study emphasize on routine carotid screening in high-risk populations to inform targeted preventive strategies.